Infant formula containing large, milk phospholipid-coated lipid droplets and dairy lipids affects cognitive performance at school age - Schipper, Lidewij; Bartke, Nana; Marintcheva-Petrova, Maya; Schoen, Stefanie; Vandenplas, Yvan; Hokken-Koelega, Anita C. S. (Frontiers in Nutrition, 2023)
Background: Breastfeeding has been positively associated with infant and child neurocognitive development and function. Contributing to this effect may be differences between human milk and infant formula in the milk lipid composition and milk fat globule structure.Objective: To evaluate the effects of an infant formula mimicking human milk lipid composition and milk fat globule structure on childhood cognitive performance.Methods: In a randomized, controlled trial, healthy term infants received until 4 months of age either a Standard infant formula (n=108) or a Concept infant formula (n=115) with large, milk phospholipid coated lipid droplets and containing dairy lipids. A breastfed reference group (n=88) was included. Erythrocyte fatty acid composition was determined at 3 months of age. Neurocognitive function was assessed as exploratory follow-up outcome at 3, 4 and 5 years of age using the Flanker test, Dimensional Change Card Sort (DCCS) test and Picture Sequence Memory test from the National Institutes of Health Toolbox Cognition Battery. Mann-Whitney U test and Fisher exact test were used to compare groups.Results: Erythrocyte omega-6 to -3 long-chain polyunsaturated fatty acid ratio appeared to be lower in the Concept compared to the Standard group (P = 0.025). At age 5, only the Concept group was comparable to the Breastfed group in the highest reached levels on the Flanker test, and the DCCS computed score was higher in the Concept compared to the Standard group (P = 0.021).Conclusion: These outcomes suggest that exposure to an infant formula mimicking human milk lipid composition and milk fat globule structure positively affects child neurocognitive development. Underlying mechanisms may include a different omega-3 fatty acid status during the first months of life.The trial and follow-up trial are registered in the Dutch Trial Registry (NTR3683 and NTR5538).